2007
DOI: 10.1002/hlca.200790058
|View full text |Cite
|
Sign up to set email alerts
|

Model Construction for the A–B–C Ring System of Lysergic Acid via Vilsmeier–Haack‐Type Cyclization of 1H‐Indole‐4‐propanoic Acid Derivatives

Abstract: Vilsmeier -Haack-type cyclization of 1H-indole-4-propanoic acid derivatives was examined as model construction for the A -B -C ring system of lysergic acid (1). Smooth cyclization from the 4 position of 1H-indole to the 3 position was achieved by Vilsmeier -Haack reaction in the presence of K 2 CO 3 in MeCN, and the best substrate was found to be the N,N-dimethylcarboxamide 9 ( Table 1). The modified method can be successfully applied to an a-amino acid derivative protected with an N-acetyl function, i.e., to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
6
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 25 publications
1
6
0
Order By: Relevance
“…The mesyl group could not be displaced by treatment with LiEt 3 BH but did react with sodium thiophenolate to give the corresponding thioether as a mixture of ( Z )- 13 and ( E )- 14 isomers (Scheme ). In an attempt to reduce the number of steps involved in this synthesis, the alcohol 12 was displaced directly by diphenyldisulfide and tributylphosphine rather than going through the mesylate (Scheme ) . It was observed that this reaction also resulted in isomerization of the C-11−C-12 double bond to form the separable Z - and E -isomers 13 and 14 , respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The mesyl group could not be displaced by treatment with LiEt 3 BH but did react with sodium thiophenolate to give the corresponding thioether as a mixture of ( Z )- 13 and ( E )- 14 isomers (Scheme ). In an attempt to reduce the number of steps involved in this synthesis, the alcohol 12 was displaced directly by diphenyldisulfide and tributylphosphine rather than going through the mesylate (Scheme ) . It was observed that this reaction also resulted in isomerization of the C-11−C-12 double bond to form the separable Z - and E -isomers 13 and 14 , respectively.…”
Section: Resultsmentioning
confidence: 99%
“…In an attempt to reduce the number of steps involved in this synthesis, the alcohol 12 was displaced directly by diphenyldisulfide and tributylphosphine rather than going through the mesylate (Scheme 3). 26 It was observed that this reaction also resulted in isomerization of the C-11-C-12 double bond to form the separable Z-and E-isomers 13 and 14, respectively. This isomerization was thought to have occurred by attack of the thiophenolate ion at C-11 of 13, followed by bond rotation around the C-11-C-12 bond and then elimination of the thiophenolate ion, as illustrated by the mechanism in Scheme 4.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, compound 1 was identified as an unusual phenylamine-incorporated angucyclinone (2-(2-(hydroxymethyl)-3-methoxyphenyl)-7-methyl-1-phenylbenzo­[ cd ]­indol-3­(1 H )-one) (Figure ). Until now, only a few compounds containing a benzo­[ cd ]­indol-3­(1 H )-one moiety have been reported, with 0231A and 0231B as the only two natural products, and all others as intermediates in the total synthesis of 0231B or ergot alkaloids . Therefore, compound 1 represents a new member of angucyclinones featuring a unique 1-phenylbenzo­[ cd ]­indol-3­(1 H )-one moiety.…”
mentioning
confidence: 99%
“…The benzo­[ cd ]­indol-3­(1 H )-one ring system has been synthesized in the total synthesis of 0231B and ergot alkaloids. There are four methods reported to construct this ring system, with all of them needing catalysts and some needing very low (−78 °C) or high (80 °C) temperatures (Figure S7). The discovery of nonenzymatic conversion from 2 to 1 in this work provides a more mild and efficient method to construct the benzo­[ cd ]­indol-3­(1 H )-one ring system (Figure C).…”
mentioning
confidence: 99%
“…However, the hydrogenation of cyclic α-acyl enamides, especially those bearing an endocyclic α-acyl group, remains uncommon (Figure , red-colored structures, X = C, N, O, S). , On the other hand, compared to the extensive research carried out with α-dehydroamino acids, esters, and amides, only one report has been published concerning the asymmetric hydrogenation of α-dehydroamino ketones and none for cyclic substrates, though chiral cyclic α-amino ketones are very useful structural motifs found in a range of bioactive molecules and can be easily derivatized to give versatile chiral cyclic β-amino alcohols and amines . Previously, chiral cyclic α-amino ketones were typically synthesized via intramolecular Friedel–Crafts reactions of chiral α-amino acids and via α-aminations of cyclic ketones or their equivalents. In addition to these procedures being inefficient, these methodologies also suffer from problems of partial racemization of the chiral α-amino ketones because of their facile enolization under acidic and alkaline conditions. Therefore, from both theoretical and practical perspectives, synthesis of chiral cyclic α-amino ketones via the asymmetric hydrogenation of cyclic α-dehydroamino ketones with high chemoselectivity (distinguish the reductive CC and CO bonds) and enantioselectivity is greatly desired.…”
mentioning
confidence: 99%